The Tendency of Press Release Content of Makassar City Public Relations in Reporting Danny Pomanto Activities Outside His Position as Mayor - Ibnu Kasir Amahoru; M Iqbal Sultan; Muliadi Mau (Jurnal sosial dan sains, 2024)
ABSTRACT Background: The Public Relations of the Makassar City Government not only conveys positive information about the programs and policies of the Makassar City Government, but also monitors and reports on Danny Pomanto's personal activities related to his candidacy for Governor of South Sulawesi in 2024. Purpose: This research aims to analyse the tendency of Makassar City Public Relations Press Release Content in reporting Danny Pomanto's activities outside his position as Mayor of Makassar. Method: The approach used is descriptive qualitative approach with content analysis method. The unit of analysis used in this research is the press release of the Public Relations (City Government) of Makassar City Government starting from the period February 2023 to September 2023. Data analysis uses the Krippendorff method with steps of unititisation, sampling, recording, analysis, inference and data reduction Results: The results showed that the content of press releases made by the Public Relations of Makassar City Government is not only conveying positive information about the programmes and policies of Makassar City Government to the public, but the PR also oversees and reports on Danny Pomanto's activities outside of his position as mayor, including releasing his personal activities as Chair of the Hasanuddin University Alumni Association (IKA) South Sulawesi when visiting several regions in South Sulawesi which have something to do with running as a candidate for Governor of South Sulawesi 2024. Conclusion: The implication of the findings of this research that needs to be underlined is that the public relations of Makassar City Government as a representative of government institutions / agencies should only report on the activities of institutions or leaders of institutions, not to become campaigners for individual leaders of institutions for political purposes. For this reason, public relations must be neutral and not be involved in practical politics, especially ahead of the South Sulawesi Governor election.